Optimalisasi Penggunaan Pendingin Ruangan Sistem Kelas Cerdas - David Habsara Hareva; Andre Wirawan; Benn y Hardjono (Ikatan Ahli Informatika Indonesia, 2020)
Optimizing the use of electronic devices such as air conditioning is very important to avoid high costs due to the use of electricity in classrooms. This can be done by regulating its use only when the classroom is in use. There are two sufficient conditions to arrange it, namely when there is a teaching schedule and there are students in the class. By utilizing IoT technology, a cooling control system to regulate electricity usage such as air conditioning can be done. The IoT device used is a laser sensor or PIR to detect the presence of people, temperature, and humidity sensors, infrared sensors to turn the cooling system on or off. All sensors are connected to the Arduino microcontroller which forwards the collected data to the Firebase database via the internet. Android smartphones are used to embed smart class applications that control the cooling system control configuration, monitor, and view the history of cooling system usage via data stored in Firebase. When creating a class schedule consisting of class names and class usage time, there is a threshold for the minimum number of students in the class to regulate 2 cooling system devices. The detection test for the presence of students entering and leaving the classroom was carried out using a laser sensor and a PIR sensor with a success rate of 50% and 100% respectively, for 10 consecutive attempts, although the laser sensor is more accurate, it requires accurate sensor placement as well forget better results. The cooling control system was tried out for 5 days, Monday - Friday, based on a simulated classroom usage schedule, two cooling systems that were active for 7.5 hours from 60 hours per week, or the equivalent of 13% of the total active and inactive class time. The electricity cost incurred for only 2 coolers is IDR 54,960 / month compared to the total expenditure of IDR 439,680 / month, or equivalent to IDR 43,968,000 for 100 rooms / month. The built-in cooling control system can overcome high costs due to turning on the cooling system when not in use.